Detecting spirit-levelling errors in the AHD: recent findings and issues for any new Australian height datum - Filmer, Michael; Featherstone, Will (Taylor & Francis Ltd, 2009)
The Australian Height Datum (AHD) forms the vertical geodetic datum for Australia and is thus the framework for all heights, including those used to establish digital elevation models (DEMs). The AHD was established over quite a short timeframe, due to the urgent requirement for height control for topographic mapping and gravity surveys. This necessitated the use of lower quality spirit-levelling observations over long distances and approximate data reductions. Geoscience Australia has kindly supplied us with height differences for all sections of the basic and supplementary spirit-levelling used to establish the AHD, allowing us to analyse loop closures to detect spirit-levelling (or data entry / transcription) errors in this dataset. In the case-studies presented here, we show that GPS and a precise gravimetric quasigeoid model can be used to identify the sections in a levelling loop that cause misclosure, reflecting the relative quality of modern quasigeoid models over the spirit-levelling originally used to establish the AHD. We also consider and discuss some of the other issues that would have to be considered if Australia is to implement a new vertical geodetic datum from these data to support, for example, improved DEMs in the future.